Secrets of the Snow : Visual Clues to Avalanche and Ski Conditions - LaChapelle, Edward R. (Book collections on Project MUSE., 2001)
"Secrets of the Snow is an overview of the easily visible aspects of snow in the alpine mountain landscape. It describes visible snow features and textures arising from climate, wind-drift, layering, solar radiation, and melting, and explains how snow may be "read" for information on avalanche formation and suitability for winter sports."--Jacket